Exosomes derived from miR-146a-overexpressing fibroblast-like synoviocytes in cartilage degradation and macrophage M1 polarization: a novel protective agent for osteoarthritis? - Wang, Huan; Zhang, Yue; Zhang, Chengfei; Zhao, Yan; Shu, Jun; Tang, Xuezhang (Frontiers in Immunology, 2024)
Pathological changes in the articular cartilage (AC) and synovium are major manifestations of osteoarthritis (OA) and are strongly associated with pain and functional limitations. Exosome-derived microRNAs (miRNAs) are important regulatory factors in intercellular communication and can affect the progression of OA by participating in chondrocyte degradation and phenotypic transformation in the polarization of synovial macrophages. However, the specific relationship and pathway of action of exosomal miRNAs in the pathological progression of OA in cartilage and the synovium remain unclear. The current study found that fibroblast-like synoviocyte (FLS)-derived exosomes (FLS-Exos), under the influence of miR-146a, may be a novel biological factor regulating AC degradation and synovial macrophage polarization. The targeted relationship between miR-146a and TRAF6 was evaluated in vivo and in vitro, and the involvement of the relevant NF-κB signaling pathway was also assessed. The possible molecular mechanisms underlying these effects were analyzed. The expression of miR-146a in the synovial exosomes of OA rats was significantly higher than that of healthy rats. In vitro, the upregulation of miR-146a reduced the apoptosis of chondrocytes, whereas its downregulation had the opposite effect. In vivo, exosomes derived from miR-146a-overexpressing FLSs (miR-146a-FLS-Exos) reduced AC injury and chondrocyte apoptosis in OA. Synovial proliferation was reduced and the polarization of synovial macrophages from M1 to M2 was induced. Mechanistically, the expression of TRAF6 was inhibited by targeting miR-146a, thereby participating in the regulation of the Toll-like receptor 4/TRAF6/NF-κB pathway in the innate immune response. In conclusion, the results suggest that miR-146a may affect cartilage degradation and macrophage M1 polarization through FLS-Exos, alleviate the progression of OA by participating in the targeted regulation of the innate immune NF-κB pathway, and may be a novel protective agent for OA. This study elucidates the role of exosomal miRNAs and their therapeutic value in OA.